Studi Etnofarmakognosi- Etnofarmakologi Tumbuhan Sebagai Obat Di Kampung Naga Kecamatan Salawu Kabupaten Tasikmalaya - Ria Mariani (Universitas Bhakti Kencana, 2015)
The study of ethnopharmacognosy â€“ ethnopharmacology of traditional usage of herbal medicine in â€œKampung Naga Kecamatan Salawu Kabupaten Tasikmalayaâ€ had been studied. Method of this study contained of distric and ethnopharmacognosy â€“ ethnopharmacology studies.It showed that there were 28 family of plants and 51 species that identified used as traditional medicine in â€œKampung Nagaâ€, which Asteraceae was the most used. Imunostimulant was the most used utillity among those plants. Leaves was the most used part of those plants. Garden is the most collected among the others. Boiled in the water was the most drug processing used.